2022
DOI: 10.1039/d1fo02579a
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin alleviated cerebral ischemia/reperfusion injuryin vivoandin vitroby inhibiting oxidative stressviathe SIRT1/Nrf2 signaling pathway

Abstract: Oxidative stress is known to play a pivotal role in the pathogenesis of cerebral ischemia reperfusion (I/R) injury. Accumulating studies have revealed that diosmetin (Dios) could protect against oxidative stress...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…These data strongly suggest that injury of testicular spermatogenesis after testicular ischemia-reperfusion is due to overproduction of reactive oxygen species. Previous studies have demonstrated that treatment with reactive oxygen species scavengers can reduce ischemia-reperfusion injury in the liver, kidney, heart, brain, and so on [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data strongly suggest that injury of testicular spermatogenesis after testicular ischemia-reperfusion is due to overproduction of reactive oxygen species. Previous studies have demonstrated that treatment with reactive oxygen species scavengers can reduce ischemia-reperfusion injury in the liver, kidney, heart, brain, and so on [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SIRT1 regulated mitochondrial function and antioxidant defenses through activation of transcriptional coactivator PPAR-γ co-activator1α (PGC-1α) and activities and the anti-oxidant enzyme SOD after brain ischemic damage in rats subjected to transient middle cerebral artery occlusion (tMCAO), a classic FCI animal model ( Li et al, 2021 ). SIRT1 could inhibit oxidative stress in the tMCAO rats by activation of Nrf2, NQO1, and HO-1, which are important factors mediating oxidative stress response ( Mei et al, 2022 ). Besides, the SIRT1/FOXO1 pathway was also reported to be activated by SIRT1 to alleviate excess oxidative injury.…”
Section: Role Of Silent Information Regulator 1 In Cerebral Ischemia-...mentioning
confidence: 99%
“…In addition, our results also found that inhibiting SIRT1 activation could result in ferroptosis in dNCR mice. SIRT1 plays an important role in neurodegenerative diseases and cognitive deficits via regulating the levels of Nrf2 and HO-1 [1,[73][74][75][76]. The activation of SIRT1 targeting Nrf2/HO-1 pathway activation can alleviate central nervous system inflammation-induced cognitive deficits [73].…”
Section: Discussionmentioning
confidence: 99%